FORMULASI KRIM SARI BUAH MARKISA KUNING (Passiflora edulis L var. Flavicarpa Degener) SEBAGAI ANTI-AGING - Sitorus, Elly Nurita; Thaib, Cut Masyithah; Sianipar, Artha Yuliana (Jurnal Farmanesia, 2021)
On the outer surface of the skin there are pores (cavities) where sweat is released. The skin has many functions, as a protector of the body from various things that can be harmful, as a sense of touch, and as a regulator of body temperature.